Preparation method of Fe-based nanocrystalline alloy ribbon, preparation method of magnetic core, Fe-based nanocrystalline alloy ribbon and magnetic core

During the preparation process of the Fe-based nanocrystal alloy thin strip, the Fe-based alloy molten liquid is provided on the rotary cooling roller and quenched solidification and heat treatment are carried out, the emergence of protrusions on the free solidification surface is suppressed, the problem of reducing insulation in the magnetic core is solved, and the core preparation with high insulation and low eddy current loss is achieved.

CN112585703BActive Publication Date: 2025-03-11PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980054760.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-26
Filing Date
2019-09-24
Publication Date
2025-03-11
Estimated Expiration
2039-09-24

AI Technical Summary

Technical Problem

When the prior art thins the Fe-based nanocrystal alloy thin strip, protrusions occur on the one-sided main surface of the alloy thin strip, causing contact and conduction of the alloy thin strip adjacent to the core intermediary insulation layer to reduce insulation.

Method used

By providing the Fe-based alloy molten liquid to the rotating cooling roller, it is quenched and solidified, a thin strip of Fe-based amorphous alloy having a free solidification surface and a roller contact surface is obtained, and heat-treated is performed to suppress the generation of protrusions in the free solidification surface. The outer peripheral portion of the cooling roller is composed of Cu alloy, and the thermal conductivity is controlled to be 70W/(m·K) or more than 225W/(m·K) to suppress the generation of protrusions.

Benefits of technology

The generation of protrusions is suppressed in the thin strip of Fe-based nanocrystalline alloy, and the insulation between the adjacent thin strips of Fe-based nanocrystalline alloys with the magnetic core intermediary insulation layer is improved, thereby reducing eddy current losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112585703B_ABST
    Figure CN112585703B_ABST
Patent Text Reader

Abstract

Provided is a method for preparing an Fe-based nanocrystalline alloy ribbon, comprising the following steps: providing a Fe-based alloy molten liquid onto a rotating cooling roller, rapidly solidifying the Fe-based alloy molten liquid provided onto the cooling roller to obtain an Fe-based amorphous alloy ribbon having a free solidification surface and a roller contact surface, and heat-treating the Fe-based amorphous alloy ribbon to obtain an Fe-based nanocrystalline alloy ribbon, wherein the outer periphery of the cooling roller is composed of a Cu alloy, and the thermal conductivity of the outer periphery is not less than 70 W / (m·K) and not more than 225 W / (m·K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for preparing a Fe-based nanocrystalline alloy ribbon, a method for preparing a magnetic core, a Fe-based nanocrystalline alloy ribbon and a magnetic core. Background Art

[0002] Fe-based nanocrystalline alloys have excellent magnetic properties such as low loss and high magnetic permeability, and are therefore used as a raw material for magnetic parts (eg, magnetic cores).

[0003] A magnetic core comprising an Fe-based nanocrystalline alloy ribbon is prepared, for example, by the following method, i.e., a Fe-based alloy molten liquid is rapidly solidified by a single-roll method to obtain an Fe-based amorphous alloy ribbon, and the obtained Fe-based amorphous alloy ribbon is heat-treated after winding or stacking so that nanocrystalline grains are precipitated in the alloy structure of the Fe-based amorphous alloy ribbon to serve as an Fe-based nanocrystalline alloy ribbon (for example, refer to Patent Document 1).

[0004] As a magnetic core containing an Fe-based nanocrystalline alloy strip, for example, Patent Document 2 discloses a low-loss high-frequency acceleration cavity magnetic core used as a high-frequency acceleration cavity magnetic core, which is a high-frequency acceleration cavity magnetic core having the following shape, i.e., a Fe-based nanocrystalline alloy strip having a roller contact surface and a free surface obtained by a single-roll method is wound with an insulating layer interposed therebetween, and protrusions of a predetermined shape are dispersed on the free surface of the Fe-based nanocrystalline alloy strip, and the tops of the protrusions are polished and passivated.

[0005] Patent Document 1: Japanese Patent Publication No. 4-4393

[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-167228 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Patent Document 2 states that when the thickness of an alloy strip having a thickness of more than 15 μm is reduced, a protrusion is formed on one main surface of the alloy strip, and no insulating layer is formed on the protrusion. As a result, the adjacent alloy strips are in contact and conduction with each other through the insulating layer in the magnetic core, thereby causing a problem of reduced insulation. Patent Document 2 states that the above problem can be solved by grinding and passivating the top of the protrusion.

[0009] However, the method of grinding and passivating the top of the protrusion described in patent document 2 has the problem of increasing production time. In addition, there is also the problem of large maintenance time of grinding capacity. In addition, it is difficult to continue to grind effectively without deviation on the whole surface of almost all Fe-based nanocrystalline alloy ribbons, and therefore, there is a limit in ensuring continuous stable high insulation.

[0010] Therefore, as a technology for improving protrusions in a thin Fe-based nanocrystalline alloy ribbon (specifically, a thickness of 15 μm or less), a technology that does not rely on grinding the top of the protrusion but suppresses the occurrence of the protrusion itself is required.

[0011] The first aspect of the present disclosure is to provide a method for preparing an Fe-based nanocrystalline alloy ribbon, which is a Fe-based nanocrystalline alloy ribbon with a relatively thin thickness. The preparation method can prepare an Fe-based nanocrystalline alloy ribbon that suppresses the occurrence of protrusions in the free solidification surface.

[0012] The second aspect of the present disclosure is to provide a method for preparing a magnetic core, which is a magnetic core comprising a wound body obtained by winding a thin Fe-based nanocrystalline alloy strip with an insulating layer interposed therebetween, and can prepare a magnetic core with excellent insulation between adjacent Fe-based nanocrystalline alloy strips with an insulating layer interposed therebetween.

[0013] A third aspect of the present disclosure is to provide an Fe-based nanocrystalline alloy ribbon having a relatively thin thickness and in which the occurrence of protrusions in a free solidification surface is suppressed.

[0014] A fourth aspect of the present disclosure is to provide a magnetic core comprising a wound body obtained by winding a thin Fe-based nanocrystalline alloy ribbon with an insulating layer interposed therebetween, wherein the insulating properties between adjacent Fe-based nanocrystalline alloy ribbons with the insulating layer interposed therebetween are excellent.

[0015] Solution to the problem

[0016] The specific methods used to solve the above problems are as follows:

[0017] <1> A method for preparing a Fe-based nanocrystalline alloy ribbon comprises the following steps:

[0018] The step of supplying a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid supplied onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm, and

[0019] The step of heat treating the Fe-based amorphous alloy ribbon to obtain a Fe-based nanocrystalline alloy ribbon;

[0020] The outer peripheral portion of the cooling roller is made of a Cu alloy, and the thermal conductivity of the outer peripheral portion is not less than 70 W / (m·K) and not more than 225 W / (m·K).

[0021] <2> According to the above <1> The method for preparing the Fe-based nanocrystalline alloy thin strip described in the item, wherein the Vickers hardness of the peripheral portion is greater than 250 HV.

[0022] <3> According to the above <1> or <2> The method for preparing the Fe-based nanocrystalline alloy thin strip described in item 1, wherein the Fe-based alloy molten liquid has an alloy composition represented by the following composition formula (A),

[0023] Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A)

[0024] In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.40.

[0025] <4> A method for preparing a magnetic core, the magnetic core comprising a winding body C obtained by winding a Fe-based nanocrystalline alloy thin strip through an insulating layer, comprising the following steps:

[0026] The step of providing a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid provided onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm,

[0027] The step of forming the insulating layer on the free solidification surface of the Fe-based amorphous alloy thin strip,

[0028] The step of winding the Fe-based amorphous alloy thin strip formed with the insulating layer to obtain a winding body A formed by winding the Fe-based amorphous alloy thin strip through the insulating layer, and

[0029] The step of heat treating the wound body A to obtain the wound body C,

[0030] The outer peripheral portion of the cooling roller is made of a Cu alloy, and the thermal conductivity of the outer peripheral portion is not less than 70 W / (m·K) and not more than 225 W / (m·K).

[0031] <5> according to <4> The method for preparing the magnetic core described in the item, wherein the Vickers hardness of the outer peripheral portion is greater than 250 HV.

[0032] <6> according to <4> or <5> The method for preparing a magnetic core according to item 1, wherein the Fe-based alloy molten liquid has an alloy composition represented by the following composition formula (A),

[0033] Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A)

[0034] In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.40.

[0035] <7> An Fe-based nanocrystalline alloy thin strip having a free solidification surface and a roller contact surface, wherein the number of protrusions P having a pit in the center of the free solidification surface is 100 mm 2 The area is 1.2 or less, the width of the Fe-based nanocrystalline alloy ribbon is 5 mm to 65 mm, and the thickness is 10 μm to 15 μm.

[0036] <8> according to <7> The Fe-based nanocrystalline alloy ribbon described in the item has a warp in the width direction of not more than 0.30 mm per 10 mm width.

[0037] <9> according to <7> or <8> The Fe-based nanocrystalline alloy ribbon described in item 1 has an alloy composition represented by the following composition formula (A):

[0038] Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A)

[0039] In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.40.

[0040] <10> A magnetic core comprising <7> to <9> A wound body C1 formed by winding the Fe-based nanocrystalline alloy thin strip described in any one of the above through an insulating layer.

[0041] <11> according to <10> The magnetic core described in item 1 has an insulation ratio RI represented by the following formula (1) of 80% or more,

[0042] RI=Rr / (Ru·Lr)×100(%)…Equation (1)

[0043] In formula (1), Rr represents the DC resistance value (Ω) between the innermost end and the outermost end of the Fe-based nanocrystalline alloy strip, Ru represents the DC resistance value (Ω) of the Fe-based nanocrystalline alloy strip per 1 m in the length direction, and Lr represents the length (m) of the Fe-based nanocrystalline alloy strip in the length direction.

[0044] Effects of the Invention

[0045] According to a first aspect of the present disclosure, a method for preparing an Fe-based nanocrystalline alloy ribbon is provided. The Fe-based nanocrystalline alloy ribbon is a Fe-based nanocrystalline alloy ribbon with a relatively thin thickness. The preparation method can prepare an Fe-based nanocrystalline alloy ribbon that suppresses the occurrence of protrusions in a free solidification surface.

[0046] According to the second aspect of the present disclosure, a method for preparing a magnetic core is provided, which is a magnetic core comprising a wound body obtained by winding a thinner Fe-based nanocrystalline alloy strip through an insulating layer, and can prepare a magnetic core with excellent insulation between adjacent Fe-based nanocrystalline alloy strips through an insulating layer.

[0047] According to a third aspect of the present disclosure, there is provided an Fe-based nanocrystalline alloy ribbon having a relatively thin thickness and in which the occurrence of protrusions in a free solidification surface is suppressed.

[0048] According to a fourth aspect of the present disclosure, a magnetic core is provided, which includes a wound body obtained by winding a thin Fe-based nanocrystalline alloy strip through an insulating layer, and is a magnetic core with excellent insulation between adjacent Fe-based nanocrystalline alloy strips through the insulating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a laser microscope image (magnification 50 times) of two protrusions P (ie, protrusions P having a pit in the center) in the Fe-based amorphous alloy ribbon of Comparative Example 1 observed from a direction perpendicular to the free solidification plane.

[0050] Figure 2 yes Figure 1 3D view of the . DETAILED DESCRIPTION

[0051] In the present disclosure, the term "step" refers not only to an independent step but also to a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step is achieved.

[0052] In the present disclosure, the so-called "nanocrystalline alloy" refers to an alloy containing a nanocrystalline phase (ie, a phase formed by nanocrystalline particles). The "nanocrystalline alloy" may also contain a phase other than the nanocrystalline phase (eg, an amorphous phase).

[0053] In the present disclosure, the term "Fe-based" means that the main component (ie, the component containing the largest mass) is Fe.

[0054] [Method for preparing Fe-based nanocrystalline alloy ribbon]

[0055] The method for preparing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention comprises the following steps:

[0056] The step of supplying a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid supplied onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm, and

[0057] The step of heat treating the Fe-based amorphous alloy ribbon to obtain a Fe-based nanocrystalline alloy ribbon;

[0058] The outer peripheral portion of the cooling roller is made of a Cu alloy, and the thermal conductivity of the outer peripheral portion is not less than 70 W / (m·K) and not more than 225 W / (m·K).

[0059] The method for preparing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention may further include other steps as required.

[0060] In the present disclosure, the free solidification surface of the Fe-based amorphous alloy ribbon refers to the main surface of the two main surfaces of the Fe-based amorphous alloy ribbon that is not in contact with the cooling roller and is exposed to the atmosphere during the preparation of the Fe-based amorphous alloy ribbon. The free solidification surface of the Fe-based nanocrystalline alloy ribbon obtained by heat treating the Fe-based amorphous alloy ribbon also has the same meaning.

[0061] In the present disclosure, the roller contact surface of the Fe-based amorphous alloy thin strip refers to the main surface of the two main surfaces of the Fe-based amorphous alloy thin strip that contacts the cooling roller during the preparation of the Fe-based amorphous alloy thin strip. The roller contact surface of the Fe-based nanocrystalline alloy thin strip obtained by heat treating the Fe-based amorphous alloy thin strip also has the same meaning.

[0062] The alloy strip having a free solidification surface and a roll contact surface means that the alloy strip is obtained by a single roll method.

[0063] Through research conducted by the present inventors, it has been determined that when a Fe-based alloy molten liquid is provided to a rotating cooling roller so that the provided Fe-based alloy molten liquid is rapidly solidified, a Fe-based amorphous alloy strip having a free solidification surface and a roller contact surface is obtained (hereinafter, the operation up to this point is also referred to as "casting"), and when the obtained Fe-based amorphous alloy strip is heat-treated to obtain a Fe-based nanocrystalline alloy strip, particularly when the thickness of the Fe-based amorphous alloy strip is less than 15 μm and the outer periphery of the cooling roller is composed of a Cu alloy, and the thermal conductivity of the outer periphery is greater than 225 W / (m·K), protrusions are likely to form on the free solidification surface of the Fe-based nanocrystalline alloy strip.

[0064] The reasons are unknown, but the speculations are as follows:

[0065] The casting of the above-mentioned Fe-based amorphous alloy thin strip is usually carried out while grinding the outer peripheral surface (i.e., the surface of the outer peripheral portion) of the cooling roller. The grinding of the outer peripheral surface is usually carried out from the time when the cast Fe-based amorphous alloy thin strip is peeled off from the above-mentioned outer peripheral surface to the time when the subsequent Fe-based alloy molten liquid is provided to the outer peripheral surface. Here, when the outer peripheral portion of the cooling roller is composed of a Cu alloy and the thermal conductivity of the above-mentioned outer peripheral portion exceeds 225W / (m·K), there is a tendency for the Vickers hardness of the above-mentioned outer peripheral portion to be lower. As a result, it is believed that when the outer peripheral surface of the cooling roller is ground, deep scratches are easily added to the outer peripheral portion to produce coarse grinding powder, and the generated grinding powder is easy to adhere to the outer peripheral surface. When the Fe-based alloy molten liquid is provided on the outer peripheral surface with the grinding powder attached, air is easily entrained in the provided Fe-based alloy molten liquid, and as a result, it is believed that a portion that is easy to crystallize due to insufficient cooling rate is locally generated, and this portion will become a protrusion. When the thickness of the Fe-based amorphous alloy ribbon to be cast is thin (specifically, less than 15 μm), it is believed that it is more susceptible to the influence of grinding powder, and thus more likely to produce protrusions. It is believed that the produced protrusions are maintained even in the free solidification surface of the Fe-based nanocrystalline alloy ribbon obtained by heat treating the Fe-based amorphous alloy ribbon.

[0066] Regarding the above-mentioned problems, the method for producing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention is not limited to casting the Fe-based amorphous alloy ribbon having a thickness of 15 μm or less, but can also suppress the generation of protrusions in the free solidification surface.

[0067] In order to effectively suppress the generation of protrusions in the free solidification surface, it is advantageous to set the thermal conductivity of the outer periphery of the cooling roller (i.e., the outer periphery composed of the Cu alloy) to 225 W / (m·K) or less. Specifically, by setting the thermal conductivity of the outer periphery to 225 W / (m·K) or less, the Vickers hardness of the outer periphery is increased (i.e., the outer periphery becomes hard), and the generation of the above-mentioned coarse grinding powder is suppressed, and as a result, it is believed that the generation of protrusions can be suppressed.

[0068] Hereinafter, each step of the method for preparing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention will be described.

[0069] <Steps for Obtaining Fe-Based Amorphous Alloy Strip>

[0070] The step of obtaining the Fe-based amorphous alloy thin strip is to provide the Fe-based alloy molten liquid to the rotating cooling roller, so that the Fe-based alloy molten liquid provided to the cooling roller is rapidly cooled and solidified, thereby obtaining the Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of not less than 5 mm and not more than 65 mm, and a thickness of not less than 10 μm and not more than 15 μm.

[0071] (Preferred alloy composition of Fe-based alloy molten liquid)

[0072] A preferred alloy composition of the Fe-based alloy melt is an alloy composition represented by the following composition formula (A) from the viewpoint of facilitating the formation of a nanocrystalline phase in the alloy structure by heat treatment.

[0073] Each step in the method for preparing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention has no influence on the alloy composition of the alloy.

[0074] Therefore, the alloy composition of the Fe-based alloy molten liquid remains unchanged in the production of the Fe-based amorphous alloy ribbon and the Fe-based nanocrystalline alloy ribbon using the Fe-based alloy molten liquid.

[0075] That is, the alloy composition represented by the following composition formula (A) is a preferred chemical composition of a Fe-based alloy molten liquid, a preferred chemical composition of a Fe-based amorphous alloy ribbon, and a preferred chemical composition of a Fe-based nanocrystalline alloy ribbon.

[0076] Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A)

[0077] In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when the total of Fe, Cu, Si, B, Nb and C is 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.40.

[0078] Hereinafter, the alloy composition represented by composition formula (A) will be described.

[0079] Hereinafter, the atomic % indicating the content of each element refers to the atomic % of each element when the total of Fe, Cu, Si, B, Nb, and C is 100 atomic %.

[0080] Fe is an element that mainly provides soft magnetic properties.

[0081] From the viewpoint of obtaining a high saturation magnetic flux density Bs, the Fe content (atomic %) (ie, "100-abcde" in the composition formula (A)) is preferably 72.00 atomic % or more, and more preferably 74.00 atomic % or more.

[0082] Cu is an element that becomes the core of nanocrystalline grains when a Fe-based amorphous alloy ribbon is subjected to heat treatment to obtain a Fe-based nanocrystalline alloy ribbon. The heat treatment precipitates nanocrystalline grains in the alloy structure.

[0083] From the viewpoint of the relevant effects, the content of Cu (ie, "a" in the composition formula (A)) is 0.30 atomic % or more, preferably 0.80 atomic % or more, and more preferably 0.90 atomic % or more.

[0084] On the other hand, when the content of Cu exceeds 2.00 atomic %, the possibility of the presence of nanocrystalline nuclei in the Fe-based amorphous alloy ribbon before heat treatment increases, and the nanocrystalline nuclei grow and coarsen by heat treatment, and there is a risk of deterioration of magnetic properties. Therefore, the content of Cu is 2.00 atomic % or less, preferably 1.50 atomic % or less, and more preferably 1.30 atomic % or less.

[0085] Si is an effective element for reducing the crystal magnetic anisotropy of Fe, improving the soft magnetic properties, and having the ability to form an amorphous structure together with B (boron).

[0086] When the content of Si is 13.00 atomic % or more, a high amorphous forming ability can be obtained when preparing Fe-based amorphous alloy thin strips. In addition, in the nanocrystalline alloy thin strips obtained by heat treatment, a lower saturation magnetostriction can be obtained. Therefore, the content of Si (i.e., "b" in composition formula (A)) is 13.00 atomic % or more, preferably 13.40 atomic % or more, and more preferably 13.50 atomic % or more.

[0087] On the other hand, when the Si content exceeds 16.00 atomic %, the viscosity of the alloy melt decreases, so when the alloy melt is poured onto the outer peripheral surface of the cooling roll and rapidly solidified to obtain the Fe-based amorphous alloy ribbon, there is a risk of deterioration in the smoothness of the free solidification surface of the Fe-based amorphous alloy ribbon. Therefore, the Si content is 16.00 atomic % or less, preferably 15.5 atomic % or less.

[0088] As mentioned above, B (boron) is an effective element with amorphous forming ability together with Si. In addition, when forming nanocrystalline phase (i.e. the phase formed by nanocrystalline particles) in alloy structure by heat treatment, it is an element that determines the volume fraction of the amorphous phase as the phase of uncrystallization. In other words, B is an element that determines the volume ratio of the nanocrystalline phase after the heat treatment and the amorphous phase.

[0089] Compared with the magnetostriction of the nanocrystalline phase, which is negative, the magnetostriction of the amorphous phase is positive, and the ratio of the two determines the magnetostriction of the alloy as a whole. When the content of B is high, the volume fraction of the amorphous phase becomes higher than that of the nanocrystalline after heat treatment, resulting in an increase in the saturation magnetostriction. As for the saturation magnetostriction, 5×10 -6The following. From the saturation magnetostriction of 5×10 -6 From the following viewpoints, the content of B (i.e., "c" in the composition formula (A)) is 11.00 atomic % or less, preferably 9.00 atomic % or less. When the saturation magnetostriction is small, when the prepared magnetic core is housed in a housing or the like, or when a winding wire is wound around the magnetic core to form a coil, even if the magnetic core is subjected to mechanical stress, the degradation of the magnetic properties can be suppressed.

[0090] On the other hand, when the content of B is low, it becomes difficult to stably obtain an amorphous phase when the alloy melt is rapidly cooled to prepare an alloy ribbon. From the viewpoint of stably obtaining an amorphous phase, the content of B is 6.00 atomic % or more, preferably 6.50 atomic % or more.

[0091] Nb is an effective element for uniformly distributing nanocrystalline grains precipitated after heat treatment in the alloy structure, suppressing the generation of coarse grains, and precipitating fine nanocrystalline grains.

[0092] From the viewpoint of the effects involved, the Nb content (ie, "d" in composition formula (A)) is 2.00 atomic % or more, preferably 2.40 atomic % or more, more preferably 2.50 atomic % or more, and even more preferably 2.80 atomic % or more.

[0093] On the other hand, Nb does not contribute to magnetic properties, and is preferably 4.00 atomic % or less, more preferably 3.50 atomic % or less, and further preferably 3.20 atomic % or less.

[0094] C (carbon) is effective in stabilizing the viscosity of the Fe-based alloy molten liquid. From the viewpoint of the effect involved, the C content (i.e., "e" in the composition formula (A)) is 0.04 atomic % or more, preferably 0.05 atomic % or more, more preferably 0.10 atomic % or more, and further preferably 0.12 atomic % or more.

[0095] On the other hand, from the viewpoint of suppressing embrittlement of the alloy ribbon, the C content is preferably 0.40 atomic % or less, more preferably 0.35 atomic % or less, and even more preferably 0.30 atomic % or less.

[0096] The Fe-based alloy molten liquid having the alloy composition represented by composition formula (A) may further contain at least one impurity element in addition to the alloy composition (the same applies to the Fe-based amorphous alloy strip having the alloy composition represented by composition formula (A) and the Fe-based nanocrystalline alloy strip having the alloy composition represented by composition formula (A)).

[0097] Here, the impurity elements refer to elements other than the elements in the alloy composition represented by the composition formula (A).

[0098] The total content of impurity elements when the entire alloy composition represented by composition formula (A) (i.e., the total of Fe, Cu, Si, B, Nb and C) is 100 atomic % is preferably 0.20 atomic % or less, more preferably 0.10 atomic % or less.

[0099] (Cooling Roller)

[0100] In the step of obtaining the Fe-based amorphous alloy thin strip, the Fe-based alloy molten liquid is supplied to a cooling roll, and the Fe-based alloy molten liquid supplied to the cooling roll is rapidly cooled, thereby obtaining the above-mentioned Fe-based amorphous alloy thin strip.

[0101] The outer peripheral portion (ie, the portion including the outer peripheral surface) of the cooling roller is made of a Cu alloy.

[0102] The thermal conductivity of the outer peripheral portion composed of the Cu alloy is 70 W / (m·K) or more and 225 W / (m·K) or less.

[0103] By setting the thermal conductivity of the outer peripheral portion composed of the Cu alloy to 225 W / (m·K) or less, it is possible to suppress the generation of protrusions on the free solidification surface of the finally obtained Fe-based nanocrystalline alloy ribbon.

[0104] From the viewpoint of further suppressing the generation of protrusions, the thermal conductivity of the peripheral portion is preferably 220 W / (m·K) or less, more preferably 200 W / (m·K) or less, further preferably 170 W / (m·K) or less, further preferably 150 W / (m·K) or less, further preferably 130 W / (m·K) or less.

[0105] On the other hand, from the viewpoint of the performance of rapidly cooling the Fe-based alloy molten liquid supplied to the cooling roll, the thermal conductivity of the peripheral portion is 70 W / (m·K) or more. From the viewpoint of further improving the above performance, the thermal conductivity of the peripheral portion is preferably 90 W / (m·K) or more, and more preferably 110 W / (m·K) or more.

[0106] The thermal conductivity of the outer peripheral portion can be controlled by the type and amount of metal elements other than Cu contained in the Cu alloy constituting the outer peripheral portion.

[0107] For example, in the case of a Cu-Be alloy, the Be content can be controlled. As a Cu alloy having a thermal conductivity of 70 W / (m·K) to 225 W / (m·K), for example, a Cu-Be alloy containing 1.6 to 2.2 mass % of Be relative to the entire Cu-Be alloy can be cited.

[0108] In the above-mentioned Cu-Be alloy, the balance except Be is Cu and impurities. The impurities in the Cu-Be alloy are at least one of elements other than Cu and Be. As impurities in the Cu-Be alloy, Ni, Co, etc. can be listed. The total content of impurities is, for example, 1.0 mass % or less.

[0109] Furthermore, the Cu alloy constituting the outer peripheral portion may include Cu-Ni alloy, Cu-Ni-Be alloy, etc. These Cu alloys may contain impurities, and examples of the impurities include Si, Cr, Ag, Zr, and the like.

[0110] The Vickers hardness of the outer peripheral portion of the cooling roller is preferably 250 HV or more. This can further suppress the generation of protrusions on the free solidification surface.

[0111] From the viewpoint of further suppressing the generation of protrusions on the free solidification surface, the Vickers hardness of the outer peripheral portion of the cooling roll is more preferably 260 HV or more, and further preferably 300 HV or more.

[0112] The upper limit of the Vickers hardness of the outer peripheral portion of the cooling roller does not need to be particularly limited.

[0113] The Vickers hardness of the outer periphery of the cooling roller may be, for example, 400 HV or less. As a result, grinding of the outer periphery of the cooling roller becomes easier during casting (i.e., during preparation of the Fe-based amorphous alloy thin strip), and the removal of deposits attached to the outer peripheral surface of the cooling roller (i.e., the outer surface of the outer periphery) can be further improved, and crystallization of the Fe-based amorphous alloy thin strip caused by the deposits can be further suppressed.

[0114] In the present disclosure, the Vickers hardness refers to a value measured at a test load of 20 kgf.

[0115] The cooling roller preferably has a structure for cooling the outer peripheral portion inside the cooling roller. This can further suppress the temperature rise of the outer peripheral surface caused by contact with the Fe-based alloy molten liquid, and can more effectively maintain the cooling capacity of the outer peripheral surface.

[0116] As a structure for cooling the outer periphery, it is preferable to make the cooling roll rotation axis side of the outer periphery (that is, the inner surface of the outer periphery) contact with temperature-controlled water and circulate it.

[0117] In this case, the raw material of the portion of the cooling roller located on the side of the cooling roller rotating shaft when viewed from the outer periphery is preferably another alloy. There is no need to particularly consider the thermal conductivity of the other alloy. Examples of the other alloy include stainless steel, cast iron, and the like.

[0118] The thickness of the outer peripheral portion of the cooling roller is preferably 15 mm to 40 mm from the viewpoint of ensuring cooling energy for the Fe-based alloy melt and facilitating maintenance and management of the surface condition of the outer peripheral surface of the cooling roller.

[0119] The thickness of the outer peripheral portion is more preferably 17 mm or more, and further preferably 20 mm or more.

[0120] Furthermore, the thickness of the outer peripheral portion is more preferably 30 mm or less.

[0121] The diameter of the cooling roller is preferably 300 mm or more, and more preferably 400 mm or more, from the viewpoint of maintenance and management of the cooling roller body.

[0122] The diameter of the cooling roll is preferably 1000 mm or less, more preferably 900 mm or less.

[0123] In addition, from the perspective of more stably obtaining the cooling energy of the Fe-based alloy melt, the width of the cooling roller is preferably 2.5 times or more of the maximum width of the Fe-based amorphous alloy ribbon to be prepared. The width of the cooling roller is more preferably 3.0 times or more of the maximum width of the Fe-based amorphous alloy ribbon.

[0124] On the other hand, the width of the cooling roll is preferably 10.0 times or less of the maximum width of the Fe-based amorphous alloy ribbon from the viewpoint of maintaining the surface condition of the outer peripheral surface of the cooling roll.

[0125] From the viewpoint of further increasing the cooling rate of the Fe-based alloy melt and more stably preparing the Fe-based amorphous alloy thin strip, the peripheral speed of the outer periphery of the rotating cooling roller is preferably 20 m / s to 35 m / s. The peripheral speed of the outer periphery of the rotating cooling roller is more preferably 25 m / s to 35 m / s, and further preferably 27 m / s to 30 m / s.

[0126] (Width and thickness of Fe-based amorphous alloy ribbon)

[0127] In the step of obtaining the Fe-based amorphous alloy thin strip, a Fe-based amorphous alloy thin strip having a width of 5 mm to 65 mm and a thickness of 10 μm to 15 μm is obtained.

[0128] The width and thickness of the Fe-based amorphous alloy ribbon will not change due to the heat treatment described later. Therefore, the width of the Fe-based nanocrystalline alloy ribbon obtained by heat treatment of the Fe-based amorphous alloy ribbon is also 5 mm to 65 mm, and the thickness of the Fe-based nanocrystalline alloy ribbon is also 10 μm to 15 μm.

[0129] By making the thickness of the Fe-based amorphous alloy thin strip be 15 μm or less, the eddy current loss in the magnetic core produced using the Fe-based amorphous alloy thin strip can be suppressed.

[0130] In addition, as shown above, when the thickness of the Fe-based amorphous alloy ribbon is less than 15 μm, there is a tendency that protrusions are easily generated on the free solidification surface. However, according to the method for preparing the Fe-based nanocrystalline alloy ribbon disclosed in the present invention, even if the thickness is less than 15 μm, the Fe-based amorphous alloy ribbon and the Fe-based nanocrystalline alloy ribbon in which the generation of protrusions on the free solidification surface is suppressed can be obtained.

[0131] The thickness of the Fe-based amorphous alloy ribbon is preferably 14.7 μm or less, more preferably 14.5 μm or less, further preferably 14 μm or less, and further preferably 13.5 μm or less.

[0132] On the other hand, the thickness of the Fe-based amorphous alloy ribbon is 10 μm or more. Thus, a long Fe-based amorphous alloy ribbon and a long Fe-based nanocrystalline alloy ribbon can be stably obtained. Furthermore, the mechanical strength for suppressing breakage caused by the processing in the subsequent steps is ensured.

[0133] The thickness of the Fe-based amorphous alloy ribbon is preferably 11 μm or more.

[0134] In addition, by making the width of the Fe-based amorphous alloy ribbon less than 65 mm, a long Fe-based amorphous alloy ribbon and a long Fe-based nanocrystalline alloy ribbon can be stably obtained. The width of the Fe-based amorphous alloy ribbon is preferably less than 63 mm, more preferably less than 60 mm, and further preferably less than 55 mm.

[0135] On the other hand, by making the width of the Fe-based amorphous alloy ribbon 5 mm or more, productivity (economic rationality) can be ensured. The width of the Fe-based amorphous alloy ribbon is preferably 10 mm or more, and more preferably 15 mm or more.

[0136] In this step, the Fe-based amorphous alloy thin strip may be cut to adjust the width of the Fe-based amorphous alloy thin strip to be not less than 5 mm and not more than 65 mm.

[0137] In addition, multiple Fe-based amorphous alloy thin strips with a width of 5 mm to 65 mm can be obtained by cutting.

[0138] The width and thickness of the Fe-based amorphous alloy ribbon are also maintained in the Fe-based nanocrystalline alloy ribbon obtained by heat-treating the Fe-based amorphous alloy ribbon.

[0139] Therefore, the preferred ranges of the width and thickness of the Fe-based nanocrystalline alloy ribbon are the same as the preferred ranges of the width and thickness of the Fe-based amorphous alloy ribbon.

[0140] (Warping of Fe-based amorphous alloy ribbon)

[0141] The warpage of the Fe-based amorphous alloy ribbon is preferably 0.30 mm or less per 10 mm width of the Fe-based amorphous alloy ribbon.

[0142] Thus, when an insulating layer is formed on the Fe-based amorphous alloy ribbon, the uniformity of the thickness of the insulating layer (specifically, the uniformity in the width direction of the Fe-based amorphous alloy ribbon) can be further improved.

[0143] As a result, it is possible to further suppress the peeling of the insulating layer from the Fe-based amorphous alloy thin strip on which the insulating layer is formed (or the Fe-based nanocrystalline alloy thin strip obtained by heat treatment).

[0144] As a result, in the magnetic core described later, a decrease in insulation between adjacent Fe-based nanocrystalline alloy thin strips (that is, a decrease in insulation due to the peeling of the insulating layer) can be effectively suppressed.

[0145] The warpage of the Fe-based amorphous alloy thin strip per 10 mm width is more preferably 0.25 mm or less, further preferably 0.20 mm or less, and further preferably 0.10 mm or less.

[0146] The thermal conductivity of the outer peripheral portion of the cooling roller being 70 W / (m·K) or more and 225 W / (m·K) or less also contributes to reducing the warpage of the Fe-based amorphous alloy ribbon.

[0147] When the Vickers hardness of the outer peripheral portion of the cooling roll is 250 HV or more, the warpage of the Fe-based amorphous alloy ribbon is further reduced.

[0148] The warpage of the Fe-based amorphous alloy thin strip is measured by placing the Fe-based amorphous alloy thin strip on a press plate so that the convex side of the warpage faces upward, and using a device having a laser light emitting unit and a laser light receiving unit.

[0149] As the apparatus, for example, LB-300 manufactured by KEYENCE Corporation is used.

[0150] The warpage of the Fe-based amorphous alloy ribbon is maintained in the Fe-based nanocrystalline alloy ribbon obtained by heat-treating the Fe-based amorphous alloy ribbon.

[0151] Therefore, the preferred range of the warpage of the Fe-based nanocrystalline alloy ribbon is the same as the preferred range of the warpage of the Fe-based amorphous alloy ribbon.

[0152] The method for measuring the warpage of the Fe-based nanocrystalline alloy ribbon is the same as the method for measuring the warpage of the Fe-based amorphous alloy ribbon.

[0153] <Steps for Obtaining Fe-Based Nanocrystalline Alloy Strip>

[0154] In the step of obtaining the Fe-based nanocrystalline alloy ribbon, the Fe-based amorphous alloy ribbon is heat-treated to obtain the Fe-based nanocrystalline alloy ribbon.

[0155] By heat treatment, at least a part of the alloy structure of the Fe-based amorphous alloy ribbon undergoes nanocrystallization (ie, nanocrystalline grains are generated), resulting in the production of a Fe-based nanocrystalline alloy ribbon.

[0156] In the preparation method of the Fe-based nanocrystalline alloy strip disclosed in the present invention, the Fe-based amorphous alloy strip obtained by the step of obtaining the Fe-based amorphous alloy strip can be directly heat-treated, or the Fe-based amorphous alloy strip obtained by the step of obtaining the Fe-based amorphous alloy strip can be stacked or wound, and the obtained laminate or winding can be heat-treated.

[0157] The method of heat-treating the wound body obtained by winding the Fe-based amorphous alloy thin strip includes the method for producing the magnetic core of the present disclosure described below.

[0158] The maximum temperature in the heat treatment is preferably 500°C to 700°C, more preferably 550°C to 600°C.

[0159] In the heat treatment, the holding time at the highest temperature is preferably 0.3 hours to 5 hours, more preferably 0.5 hours to 3 hours, and even more preferably 1 hour to 2 hours.

[0160] The atmosphere during the heat treatment may be a non-oxidizing atmosphere such as nitrogen or the like, or may be an air atmosphere. From the viewpoint of stabilizing the quality, a non-oxidizing atmosphere is preferred.

[0161] The heat treatment is performed using, for example, a heat treatment furnace.

[0162] The heat treatment can also be carried out in a magnetic field.

[0163] [Method for preparing magnetic core]

[0164] The method for preparing a magnetic core disclosed in the present invention is a method for preparing a magnetic core comprising a winding body C obtained by winding a Fe-based nanocrystalline alloy thin strip through an insulating layer, comprising the following steps:

[0165] The step of providing a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid provided onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm,

[0166] The step of forming the insulating layer on the free solidification surface of the Fe-based amorphous alloy thin strip,

[0167] The step of winding a Fe-based amorphous alloy thin strip having an insulating layer formed thereon to obtain a wound body A formed by winding a Fe-based amorphous alloy thin strip through an insulating layer, and

[0168] The step of heat-treating the winding body A to obtain the winding body C (i.e., the winding body C obtained by winding the Fe-based nanocrystalline alloy thin strip through the insulating layer);

[0169] The outer peripheral portion of the cooling roller is made of a Cu alloy, and the thermal conductivity of the outer peripheral portion is not less than 70 W / (m·K) and not more than 225 W / (m·K).

[0170] The method for preparing the magnetic core disclosed in the present invention may further include other steps as required.

[0171] In the method for preparing the magnetic core disclosed in the present invention, the step of forming an insulating layer, the step of obtaining the winding A, and the step of obtaining the winding C are all included in the concept of "the step of obtaining the Fe-based nanocrystalline alloy strip" in the above-mentioned method for preparing the Fe-based nanocrystalline alloy strip disclosed in the present invention.

[0172] The method for preparing the magnetic core of the present disclosure is the same as the method for preparing the Fe-based nanocrystalline alloy ribbon of the present disclosure described above except for this point.

[0173] The "step of obtaining an Fe-based amorphous alloy ribbon" in the method for preparing a magnetic core disclosed in the present invention is the same as the "step of obtaining an Fe-based amorphous alloy ribbon" in the method for preparing an Fe-based nanocrystalline alloy ribbon disclosed in the present invention. Therefore, in the "step of obtaining an Fe-based amorphous alloy ribbon" in the method for preparing a magnetic core disclosed in the present invention, an Fe-based amorphous alloy ribbon in which the generation of protrusions in the free solidification surface is suppressed can also be obtained.

[0174] In the method for preparing a magnetic core disclosed in the present invention, a coil A formed by winding a Fe-based amorphous alloy ribbon through an insulating layer is subjected to heat treatment. Through the heat treatment, the Fe-based amorphous alloy ribbon in the coil A is transformed into a Fe-based nanocrystalline alloy ribbon, resulting in a magnetic core including a coil C formed by winding a Fe-based nanocrystalline alloy ribbon through an insulating layer.

[0175] As described above, the generation of protrusions in the free solidification plane is suppressed in the Fe-based amorphous alloy thin strip in the wound body A. Therefore, in the wound body C, the decrease in insulation between the Fe-based nanocrystalline alloy thin strips adjacent to each other via the insulating layer is suppressed.

[0176] As described above, in the magnetic core produced by the method for producing a magnetic core of the present disclosure, the insulation between the Fe-based nanocrystalline alloy thin strips adjacent to each other via the insulating layer is excellent.

[0177] Therefore, in the magnetic core prepared by the method for preparing the magnetic core of the present disclosure, eddy current loss is reduced.

[0178] Generally, the loss of the magnetic core is determined by hysteresis loss and eddy current loss.

[0179] Eddy current loss has frequency dependence, and has a significant tendency to increase as the applied frequency increases.

[0180] From the above viewpoints, the method for preparing a magnetic core disclosed in the present invention is particularly suitable for preparing a magnetic core used under high-frequency conditions (especially, high-frequency conditions above the MHz level).

[0181] From the viewpoint of further suppressing eddy current loss, the magnetic core produced by the method for producing a magnetic core of the present disclosure preferably has an insulation ratio RI of 80% or more. The more preferred range of the insulation ratio RI is the same as the more preferred range of the insulation ratio RI of the magnetic core according to an example of the present disclosure described below.

[0182] Hereinafter, the steps of the method for preparing the magnetic core of the present disclosure except the step of obtaining the Fe-based amorphous alloy thin strip will be described.

[0183] <Step of Forming Insulating Layer>

[0184] In the step of forming the insulating layer in the method for manufacturing the magnetic core of the present disclosure, the insulating layer is formed on the free solidification surface of the Fe-based amorphous alloy thin strip.

[0185] The insulating layer preferably contains a metal oxide such as heat-treated silicon oxide (silicon oxide), aluminum oxide (aluminum oxide), and magnesium oxide (magnesium oxide).

[0186] In this case, the metal oxide contained in the insulating layer may be one kind or two or more kinds.

[0187] When the insulating layer contains a metal oxide, the influence of the heat treatment in the step of obtaining the wound body C on the insulating layer is further reduced.

[0188] For example, the maximum temperature of the heat treatment of 550°C to 600°C exceeds the heat resistance temperature of organic materials such as polymers. Even when the heat treatment is performed at this maximum temperature, when the insulating layer contains a metal oxide, the influence of the heat treatment on the insulating layer can be reduced, and the insulating properties of the insulating layer can be effectively obtained.

[0189] The thickness of the insulating layer is preferably 1.5 to 2.5 μm.

[0190] The insulating layer may be provided on both the free solidification surface and the roller contact surface of the Fe-based amorphous alloy thin strip, but is preferably provided on the free solidification surface of the Fe-based amorphous alloy thin strip and not provided on the roller contact surface. Thus, contact between the insulating layers can be prevented in the step of obtaining the winding body and in subsequent steps, and as a result, the insulating layers can be further prevented from falling off due to contact between the insulating layers.

[0191] The insulating layer can be formed, for example, as follows.

[0192] A suspension is prepared by suspending a powdered metal oxide (hereinafter also referred to as metal oxide powder) in an organic solvent such as alcohol. An Fe-based amorphous alloy ribbon is immersed in the obtained suspension for a certain period of time to attach the suspension to the Fe-based amorphous alloy ribbon, and then the suspension attached to the Fe-based amorphous alloy ribbon is dried, thereby forming an insulating layer on the free solidification surface and the roller contact surface of the Fe-based amorphous alloy ribbon.

[0193] The thickness of the insulating layer can be determined by controlling the content of the metal oxide powder in the suspension, the immersion time, etc.

[0194] Here, when the suspension adhering to the roller contact surface is removed after taking out and before drying, the insulating layer can be formed only on the free solidification surface of the Fe-based amorphous alloy ribbon.

[0195] <Step of Obtaining Wound Body A>

[0196] In the step of obtaining the wound body A, the wound body A in which the Fe-based amorphous alloy thin strip having the insulating layer formed thereon is wound is obtained.

[0197] The Fe-based amorphous alloy thin strip having the insulating layer formed thereon can be wound up by a known method.

[0198] At this time, the wound body A may be temporarily fixed by a Cu wire having a diameter of about 0.5 mm or the like to maintain its shape.

[0199] <Step of Obtaining Wound Body C>

[0200] In the step of obtaining the wound body C, the wound body A is subjected to heat treatment to obtain the wound body C (ie, the wound body C formed by winding a Fe-based nanocrystalline alloy thin strip with an insulating layer interposed therebetween).

[0201] In the step of obtaining the wound body C, the Fe-based amorphous alloy ribbon in the wound body A is heat-treated to become an Fe-based nanocrystalline alloy ribbon. This is the same as the "step of obtaining an Fe-based nanocrystalline alloy ribbon" in the above-mentioned method for preparing an Fe-based nanocrystalline alloy ribbon of the present disclosure.

[0202] Preferred conditions for the heat treatment in the step of obtaining the wound body C are the same as the preferred conditions for the heat treatment in the "step of obtaining the Fe-based nanocrystalline alloy strip" in the method for producing the Fe-based nanocrystalline alloy strip of the present disclosure.

[0203] As indicated above, the heat treatment may be performed in a magnetic field.

[0204] As the direction of the magnetic field, two directions, namely, the circumferential direction of the magnetic core and the height direction of the magnetic core (the width of the alloy thin strip), are preferred.

[0205] The intensity of the applied magnetic field and / or the temperature range of the applied magnetic field can be appropriately adjusted according to the application of the magnetic core.

[0206] Furthermore, the order of the above two magnetic field directions can be changed.

[0207] 〔Fe-based nanocrystalline alloy ribbons, magnetic core〕

[0208] An Fe-based nanocrystalline alloy thin strip according to an example of the present disclosure has a free solidification surface and a roll contact surface, wherein the number of protrusions P having a pit in the center of the free solidification surface is 100 mm 2 The area is 1.2 or less, and the width of the Fe-based nanocrystalline alloy ribbon is 5 mm to 65 mm, and the thickness is 10 μm to 15 μm.

[0209] As described above, in the Fe-based nanocrystalline alloy ribbon according to one example of the present disclosure, the generation of protrusions in the free solidification plane is suppressed.

[0210] A magnetic core according to an example of the present disclosure includes a wound body C1 formed by winding a Fe-based nanocrystalline alloy thin strip according to an example of the present disclosure with an insulating layer interposed therebetween.

[0211] In the magnetic core according to one example of the present disclosure, the Fe-based nanocrystalline alloy thin strips adjacent to each other via the insulating layer are excellent in insulation.

[0212] As described above, in the Fe-based nanocrystalline alloy ribbon having a thickness of 15 μm or less, protrusions are easily generated on the free solidification surface, and among the protrusions, protrusions P having a pit in the center are particularly likely to be generated.

[0213] According to the research conducted by the present inventors, it was found that by limiting the protrusions P in the free solidification surface of the Fe-based nanocrystalline alloy ribbon with a thickness of 15 μm or less to 100 mm 2 In the magnetic core including the wound body C1 formed by winding the above-mentioned Fe-based nanocrystalline alloy thin strips with an insulating layer interposed therebetween, the insulation between the Fe-based nanocrystalline alloy thin strips is significantly improved.

[0214] The Fe-based nanocrystalline alloy ribbon and magnetic core according to one example of the present disclosure are completed based on this discovery.

[0215] In the present disclosure, “a wound body formed by winding a Fe-based nanocrystalline alloy thin ribbon through an insulating layer” (winding body C1, winding body C) refers to a wound body in which a Fe-based nanocrystalline alloy thin ribbon is wound through an insulating layer.

[0216] Therefore, “a wound body formed by winding a Fe-based nanocrystalline alloy thin ribbon with an insulating layer interposed therebetween” is not limited to a wound body obtained by winding a Fe-based nanocrystalline alloy thin ribbon with an insulating layer formed thereon.

[0217] For example, in the method for preparing a magnetic core disclosed above, a wound body obtained by winding a Fe-based amorphous alloy thin strip with an insulating layer is subjected to heat treatment under predetermined conditions, thereby obtaining a wound body in which a Fe-based nanocrystalline alloy thin strip is wound with an insulating layer interposed therebetween. Such a wound body is also included in the concept of "a wound body formed by winding a Fe-based nanocrystalline alloy thin strip with an insulating layer interposed therebetween".

[0218] There is no particular limitation on the method for preparing the Fe-based nanocrystalline alloy ribbon and the magnetic core according to one example of the present disclosure.

[0219] For example, according to the above-mentioned method for preparing the Fe-based nanocrystalline alloy ribbon of the present disclosure, a Fe-based nanocrystalline alloy ribbon according to an example of the present disclosure can be prepared.

[0220] In particular, according to the above-mentioned method for producing a magnetic core of the present disclosure, a magnetic core according to an example of the present disclosure can be suitably produced. In this case, as the winding C in the method for producing a magnetic core of the present disclosure, a winding C1 in a magnetic core according to an example of the present disclosure is obtained.

[0221] According to one example of the present disclosure, the protrusion P having a recess in the center (hereinafter also simply referred to as “protrusion P”) refers to a protrusion having a recess in the center when viewed from a direction perpendicular to the free solidification surface.

[0222] According to one example of the present disclosure, in order to calculate the 2 The observation of the number of protrusions P per area was performed using a stereo microscope at a magnification of 40 times.

[0223] Every 100mm of free solidification surface 2 The number of protrusions P in the area is 1.2 or less as described above. The number of protrusions P may be 0.

[0224] The number of the protrusions P is preferably 1.0 or less from the viewpoint of further improving the insulation between the Fe-based nanocrystalline alloy thin strips in the magnetic core.

[0225] The preferred embodiment of the Fe-based nanocrystalline alloy strip according to one example of the present disclosure (for example, the preferred embodiment of alloy composition, width, thickness, warpage, etc.) is the same as the preferred embodiment of the Fe-based nanocrystalline alloy strip obtained by the method for preparing the Fe-based nanocrystalline alloy strip disclosed in the present disclosure.

[0226] A preferred embodiment of the magnetic core according to one example of the present disclosure is the same as a preferred embodiment of the magnetic core obtained by the method for preparing the magnetic core of the present disclosure.

[0227] <Insulation Ratio RI>

[0228] According to the magnetic core of one example of the present disclosure, as described above, the insulation between the Fe-based nanocrystalline alloy thin strips is excellent, thereby being able to reduce eddy current loss.

[0229] From the viewpoint of further reducing eddy current loss, the insulation ratio RI represented by the following formula (1) of the magnetic core according to one example of the present disclosure is preferably 80% or more.

[0230] RI=Rr / (Ru·Lr)×100(%)…Equation (1)

[0231] In formula (1), Rr is the DC resistance value (Ω) between the innermost end and the outermost end of the Fe-based nanocrystalline alloy strip, Ru is the DC resistance value (Ω) per 1 m in the length direction of the Fe-based nanocrystalline alloy strip, and Lr is the length of the Fe-based nanocrystalline alloy strip (m).

[0232] Hereinafter, the insulation ratio RI represented by the formula (1) will be described.

[0233] In the magnetic core according to one example of the present disclosure, when the Fe-based nanocrystalline alloy thin strips are completely insulated, the product between Ru and Lr in equation (1) (ie, "Ru·Lr") is the same as Rr in equation (1). In this case, the insulation ratio RI is 100%.

[0234] On the other hand, when there is a point where insulation is broken (that is, a point where a short circuit occurs) between Fe-based nanocrystalline alloy ribbons, Rr becomes smaller than "Ru·Lr". In this case, the insulation ratio RI is less than 100%.

[0235] Ru in formula (1) can be calculated by estimating a position 1 m away from the outermost peripheral end of the magnetic core based on the diameter of the magnetic core according to one example of the present disclosure, and measuring a DC resistance value (Ω) between the outermost peripheral end and the position 1 m away from the outermost peripheral end.

[0236] From the viewpoint of further reducing eddy current loss, the insulation ratio RI of the magnetic core according to one example of the present disclosure is preferably 85% or more, and more preferably 90% or more.

[0237] In addition, the insulation ratio RI of the magnetic core according to an example of the present disclosure may be 100%, but is preferably less than 100% from the viewpoint of the manufacturing suitability (ease of production) of the magnetic core.

[0238] Example

[0239] Examples of the present disclosure are given below, but the present disclosure is not limited to the following examples.

[0240] (Example 1)

[0241] -Preparation (casting) of Fe-based amorphous alloy ribbons-

[0242] will have Fe bal. Cu 0.98 Si 14.99 B 6.68 Nb 2.89 C 0.05 An Fe-based alloy molten liquid (9.1 kg) having an alloy composition represented by (atomic %) is provided onto a rotating cooling roller, and the provided Fe-based alloy molten liquid is rapidly solidified to obtain an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface and with a width of 25 mm and a thickness of 13.4 μm.

[0243] Here, "bal." (balance) is a value corresponding to "100-abcde" in composition formula (A).

[0244] The obtained Fe-based alloy ribbon is an Fe-based amorphous alloy ribbon, that is, the alloy structure is formed of an amorphous phase, which can be confirmed by observing the cross section of the ribbon with a scanning electron microscope (SEM).

[0245] Throughout all the steps of this embodiment, the alloy composition of the Fe-based alloy does not change. Therefore, the alloy compositions of the Fe-based alloy melt, the Fe-based amorphous alloy ribbon, and the Fe-based nanocrystalline alloy ribbon described later are the same.

[0246] In addition, in all steps of the present embodiment, the size (thickness, width and length) of the thin strip does not change. Therefore, the size (thickness, width and length) of the Fe-based nanocrystalline alloy thin strip described later is the same as the size (thickness, width and length) of the Fe-based amorphous alloy thin strip.

[0247] Hereinafter, the term “ribbon” simply refers to an Fe-based nanocrystalline alloy ribbon or an Fe-based amorphous alloy ribbon.

[0248] The rotation speed of the cooling roll was 28 m / sec in terms of the peripheral speed of the outer circumference.

[0249] As the cooling roll, the following cooling roll was used.

[0250] The cooling roller has a water passage inside thereof for circulating cooling water as a structure for cooling the outer peripheral portion.

[0251] -Cooling Roller-

[0252] Diameter: 800mm

[0253] Width: 150mm

[0254] ·Thickness of outer periphery: 20mm

[0255] · Material of the outer periphery: Cu-Be alloy (Be: 1.9% by mass, the balance is Cu and impurities)

[0256] Thermal conductivity of the outer periphery: 124W / (m·K)

[0257] - Vickers hardness of the outer periphery -

[0258] The Vickers hardness of the outer periphery was measured using a Vickers hardness tester at a test load of 20 kgf.

[0259] The results are shown in Table 1.

[0260] - Every 100mm in the free solidification surface 2 Determination of the number of protrusions P in an area

[0261] In order to evaluate the number of protrusions P in the free solidification surface of the obtained Fe-based amorphous alloy thin strip, a stereomicroscope was used to observe the protrusions P at a magnification of 40 times and 30 fields of view (area 1154 mm 2 )Observe the free solidification surface.

[0262] Based on the observation results, find the 2 The number of protrusions P in the area.

[0263] The results are shown in Table 1.

[0264] The number of protrusions P in the free solidification surface of the Fe-based amorphous alloy ribbon (ie, the ribbon before heat treatment) does not change in the subsequent steps.

[0265] That is, the number of protrusions P in the free solidification surface of the Fe-based nanocrystalline alloy thin strip described later (i.e., the thin strip after heat treatment) is the same as the number of protrusions P in the free solidification surface of the Fe-based amorphous alloy thin strip (i.e., the thin strip before heat treatment).

[0266] -Warp in the width direction-

[0267] The warpage in the width direction of the Fe-based amorphous alloy ribbon is measured as follows.

[0268] One sample having a length of 100 mm was cut from each of the end portion on the casting start side and the end portion on the casting end side of the Fe-based amorphous alloy thin strip.

[0269] Each sample was placed on a press plate so that the warped convex side was on the upper side, and in this state, the height of the uppermost portion of the upper surface of the sample was measured. The height of the uppermost portion was measured using LB-300 manufactured by Keyence Corporation.

[0270] The maximum value of the height of the uppermost portion of the two samples was 0.10 mm.

[0271] The width of the sample was 25 mm, and the warpage of the Fe-based amorphous alloy ribbon in the width direction was found to be 0.04 mm per 10 mm width (see Table 1).

[0272] -Formation of insulating layer-

[0273] The following operation was performed to form an insulating layer with a thickness of 2.1 μm on the free solidification surface of the Fe-based amorphous alloy thin strip.

[0274] Silicon oxide powder having an average particle size of 0.5 μm was suspended in isopropyl alcohol (IPA) to prepare a suspension.

[0275] The Fe-based amorphous alloy ribbon obtained as described above is passed through the suspension, and then the suspension adhering to the roller contact surface of the Fe-based amorphous alloy ribbon is removed.

[0276] The suspension adhering to the free solidification surface of the Fe-based amorphous alloy thin strip was dried, thereby obtaining an insulating layer with a thickness of 2.1 μm.

[0277] - Preparation of wound body A -

[0278] The Fe-based amorphous alloy ribbon (length 264 m) with an insulating layer formed thereon was wound to obtain a wound body A having an inner diameter of 60.5 mm and an outer diameter of 100.0 mm (ie, a wound body A formed by winding the Fe-based amorphous alloy ribbon through an insulating layer).

[0279] - Preparation of winding body C (magnetic core) -

[0280] The wound body A was heat treated at a maximum holding temperature of 580° C. for 2 hours to obtain a wound body C (ie, a wound body C formed by winding a Fe-based nanocrystalline alloy thin strip through an insulating layer) as a magnetic core.

[0281] By observing the cross section of the ribbon in the wound body C with a scanning electron microscope (SEM), it was confirmed that the Fe-based alloy ribbon in the wound body C was an Fe-based nanocrystalline alloy ribbon, that is, nanocrystalline grains were generated in the alloy structure.

[0282] -Determination of insulation ratio RI-

[0283] The dielectric constant RI of the magnetic core obtained as described above (that is, the dielectric constant RI represented by the formula (1)) was measured by the above-mentioned method.

[0284] The results are shown in Table 1.

[0285] (Examples 2 to 4 and Comparative Example 1)

[0286] The production conditions of the Fe-based amorphous alloy ribbon (including the alloy composition of the Fe-based alloy melt) were the same as those of Example 1 except for the changes shown in Table 1.

[0287] However, in Examples 3 and 4, the maximum holding temperature of the heat treatment on the wound body A was further changed to 550°C.

[0288] The results are shown in Table 1.

[0289] In Example 2, the following cooling rolls were used.

[0290] The cooling roller of Example 2 also has a water passage for circulating cooling water inside as a structure for cooling the outer peripheral portion.

[0291] -Cooling Roller of Example 2-

[0292] Diameter: 800mm

[0293] Width: 150mm

[0294] ·Thickness of outer periphery: 20mm

[0295] · Material of the outer periphery: Cu-Be alloy (Be: 2.0 mass %, the balance is Cu and impurities)

[0296] Thermal conductivity of the outer periphery: 120W / (m·K)

[0297] In Example 3, the following cooling rolls were used.

[0298] The cooling roller of Example 3 also has a water passage for circulating cooling water inside as a structure for cooling the outer peripheral portion.

[0299] -Cooling Roller of Example 3-

[0300] Diameter: 450mm

[0301] Width: 300mm

[0302] ·Thickness of outer periphery: 17mm

[0303] · Material of the outer periphery: Cu-Ni alloy (Cu: 90 mass % or more, the balance is impurities (including Ni, Si and Cr))

[0304] Thermal conductivity of the outer periphery: 168W / (m·K)

[0305] In Example 4, the following cooling roll was used.

[0306] The cooling roller of Example 4 also has a water passage for circulating cooling water inside as a structure for cooling the outer peripheral portion.

[0307] -Cooling Roller of Example 4-

[0308] Diameter: 650mm

[0309] Width: 300mm

[0310] ·Thickness of outer periphery: 17mm

[0311] · Material of the outer periphery: Cu-Ni-Be alloy (Cu: 90 mass % or more, Ni: 7 mass %, Be: 0.3 mass %, the balance is impurities (including Ag, Cr and Zr))

[0312] Thermal conductivity of the outer periphery: 212W / (m·K)

[0313] In Comparative Example 1, the following cooling roll was used.

[0314] The cooling roller of Comparative Example 1 also has a water passage for circulating cooling water inside as a structure for cooling the outer peripheral portion.

[0315] -Cooling Roll of Comparative Example 1-

[0316] Diameter: 800mm

[0317] Width: 150mm

[0318] ·Thickness of outer periphery: 20mm

[0319] · Material of the outer periphery: Cu-Be alloy (Be: 0.3% by mass, the balance is Cu and impurities)

[0320] Thermal conductivity of the outer periphery: 240W / (m·K)

[0321] [Table 1]

[0322]

[0323] As shown in Table 1, in Examples 1 to 4 in which the thermal conductivity of the outer circumference of the cooling roll was 70 W / (m·K) or more and 225 W / (m·K) or less, the free solidification surface of the thin strip was reduced by 100 mm. 2 The number of protrusions P per area is small, and the insulation ratio RI of the magnetic core is excellent.

[0324] On the other hand, in Comparative Example 1 in which the thermal conductivity of the outer peripheral portion of the cooling roll exceeded 225 W / (m·K), the free solidification surface of the thin strip was 2 The number of protrusions P in the core increases significantly, and the insulation ratio RI of the core deteriorates significantly.

[0325] Figure 1 This is a laser microscope image (magnification 50 times) of two protrusions P (i.e., the protrusions P having a pit in the center) in the Fe-based amorphous alloy thin strip of Comparative Example 1 when observed from a direction perpendicular to the free solidification surface. Figure 2 express Figure 1 Here, as a laser microscope, a laser microscope "VK-8716" manufactured by Keyence Corporation was used, and the analysis software "VK Analyzer ver. 2.4.0.0" of the company was used for analysis to obtain a three-dimensional image.

[0326] In Comparative Example 1, such protrusions P were generated in large quantities, but in Examples 1 to 4, such protrusions P were reduced.

[0327] The disclosure of Japanese Patent Application No. 2018-180031 filed on September 26, 2018 is incorporated herein by reference in its entirety.

[0328] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference in the same manner as if each document, patent application, or technical standard was specifically and individually described.

Claims

1. A method for preparing a Fe-based nanocrystalline alloy ribbon, comprising the following steps: The step of supplying a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid supplied onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm, and The step of heat treating the Fe-based amorphous alloy ribbon to obtain a Fe-based nanocrystalline alloy ribbon; in, The outer peripheral portion of the cooling roller is made of a Cu alloy, the thermal conductivity of the outer peripheral portion is 110 W / (m·K) or more and 225 W / (m·K) or less, and the Vickers hardness of the outer peripheral portion is 250 HV or more and 400 HV or less. The number of protrusions P having a pit in the center portion in the free solidification surface of the Fe-based nanocrystalline alloy ribbon is 100 mm 2 Area less than 1.2, The Fe-based alloy molten liquid has an alloy composition represented by the following composition formula (A), Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A) In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.

40.

2. A method for preparing a magnetic core, the magnetic core comprising a winding body C obtained by winding a Fe-based nanocrystalline alloy thin strip through an insulating layer, comprising the following steps: The step of providing a Fe-based alloy molten liquid onto a rotating cooling roller so that the Fe-based alloy molten liquid provided onto the cooling roller is rapidly solidified, thereby obtaining an Fe-based amorphous alloy thin strip having a free solidification surface and a roller contact surface, a width of 5 mm to 65 mm, and a thickness of 10 μm to 15 μm, The step of forming the insulating layer on the free solidification surface of the Fe-based amorphous alloy thin strip, The step of winding the Fe-based amorphous alloy thin strip formed with the insulating layer to obtain a winding body A formed by winding the Fe-based amorphous alloy thin strip through the insulating layer, and A step of heat treating the wound body A to obtain the wound body C; in, The outer peripheral portion of the cooling roller is made of a Cu alloy, the thermal conductivity of the outer peripheral portion is 110 W / (m·K) or more and 225 W / (m·K) or less, and the Vickers hardness of the outer peripheral portion is 250 HV or more and 400 HV or less. The number of protrusions P having a pit in the center portion in the free solidification surface of the Fe-based nanocrystalline alloy ribbon is 100 mm 2 Area less than 1.2, The Fe-based alloy molten liquid has an alloy composition represented by the following composition formula (A), Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A) In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.

40.

3. An Fe-based nanocrystalline alloy thin strip having a free solidification surface and a roller contact surface, wherein the number of protrusions P having a pit in the center of the free solidification surface is 2 Area less than 1.2, The Fe-based nanocrystalline alloy ribbon has a width of 5 mm to 65 mm, a thickness of 10 μm to 15 μm, and a warpage in the width direction of 0.30 mm or less per 10 mm width. The Fe-based nanocrystalline alloy ribbon has an alloy composition represented by the following composition formula (A): Fe 100-a-b-c-d-e Cu a Si b B c Nb d C e …Composition formula (A) In the composition formula (A), 100-abcde, a, b, c, d and e respectively represent the atomic % of each element when Fe, Cu, Si, B, Nb and C total 100 atomic %, and a, b, c, d and e respectively satisfy 0.30≦a≦2.00, 13.00≦b≦16.00, 6.00≦c≦11.00, 2.00≦d≦4.00 and 0.04≦e≦0.

40. 4 . A magnetic core comprising a wound body C1 formed by winding the Fe-based nanocrystalline alloy thin strip according to claim 3 with an insulating layer interposed therebetween.

5. The magnetic core according to claim 4, wherein the insulation ratio RI represented by the following formula (1) is 80% or more, RI=Rr / (Ru·Lr)×100(%) Formula (1) In formula (1), Rr represents the DC resistance value in Ω between the innermost end and the outermost end of the Fe-based nanocrystalline alloy strip, Ru represents the DC resistance value in Ω per 1 m of the Fe-based nanocrystalline alloy strip in the length direction, and Lr represents the length in m of the Fe-based nanocrystalline alloy strip in the length direction.

Citation Information

Patent Citations

  • Fe-base soft magnetic alloy and its production

    JP1992004393B2

  • Dot sight

    JP2018180031A

  • Continuous producing device for metallic ribbon

    JP1982139453A

  • Alloy for low-frequency transformer and low-frequency transformer using said alloy

    JP1989242757A

  • Method and apparatus for manufacturing amorphous magnetic thin strip with excellent thickness uniformity

    JP2006281317A